Timing of seed dispersal and seed dormancy in Brazilian savanna: Two solutions to face seasonality - Escobar, Diego F.E [UNESP]; Silveira, Fernando A.O; Morellato, Leonor Patricia C [UNESP] (Oxford University Press (OUP), 2018)
Background and Aims The relationship between fruiting phenology and seed dispersal syndrome is widely recognized; however, the interaction of dormancy classes and plant life-history traits in relation to fruiting phenology and seed dispersal is understudied. Here we examined the relationship between fruiting season and seed dormancy and how this relationship is modulated by dormancy classes, dispersal syndromes, seed mass and seed moisture content in a Brazilian savanna (cerrado). Methods Dormancy classes (non-dormancy and physical, morphological, morphophysiological, physiological and physiophysical dormancy) of 34 cerrado species were experimentally determined. Their seed dispersal syndrome (autochory, anemochory, zoochory), dispersal season (rainy, dry, rainy-to-dry and dry-to-rainy transitions), seed mass and moisture contents, and the estimated germination date were also determined. Log-linear models were used to evaluate how dormancy and dormancy classes are related to dispersal season and syndrome. Key Results The proportions of dormant and non-dormant species were similar in cerrado. The communityestimated germination date was seasonal, occurring at the onset of rainy season. Overall, anemochorous nondormant species released seeds during the dry-to-rainy transition; autochorous physically dormant species dispersed seeds during the dry season and rainy-to-dry transition; zoochorous species dispersed non-dormant seeds during the dry and rainy seasons, while species with morphological, morphophysiological or physiological dormancy dispersed seeds in the transitional seasons. Seed mass differed among dispersal seasons and dormancy classes, but seed moisture content did not vary with dispersal syndrome, season or dormancy class. Conclusions The beginning of the rainy season was the most favourable period for seed germination in cerrado, and the germination phenology was controlled by both the timing of seed dispersal and seed dormancy. Dormancy class was influenced by dispersal syndrome and season. Moreover, dormancy avoided seed germination during the rainy-to-dry transition, independently of dispersal syndrome. The variability of dormancy classes with dispersal syndrome allowed animal-dispersed species to fruit all year round, but seeds germinated only during the rainy season. Conversely, seasonally restricted wind-dispersal species dispersed and germinated their non-dormant seeds only in the rainy season.
Keywords: Cerrado; dispersal syndromes; dormancy classes; fruiting phenology; germination phenology; neotropical savanna